Impacto das mudanças de uso do solo sobre as vazões máximas simuladas: estudo de caso na sub-bacia do Rio Cascavel - Bertuol, Suéllem Cristine (2021)
The West of Paraná has been highlighted nationally due to the prosperity of its economy, which has created urban growth and, consequently, an increase in the impermeable area. Thus, an analysis of the change in soil use and coverage becomes important to assess its effects on the hydrological regime of rivers, especially in areas of public water supply. Thus, the present work aims to evaluate the use and coverage of soil under the maximum flows of the Cascavel River sub-basin, responsible for part of the supply of the city of Cascavel-PR, in the last 20 years. Landsat satellite images were used to map soil use in 1999, 2009 and 2019 using ENVI 5.1 software. With the classified images and the terrain elevation model, an intense city rainfall equation is used to obtain the resulting maximum flow in the basin for each scenario using six different return periods. The maximum flow was estimated using the HEC-HMS software. The results showed an increase of 15.87% in the CN of the basin, resulting in an increase of 92,72% in the maximum flow of the basin, in the last 20 years, affecting the change in the use, and coverage of the soil in the maximum flow rates of the sub-basin.